Usage of digital reference service among students at an academic library in Northern Area / Siti Khadijah Rafie...[et al.] - Rafie, Siti Khadijah; Hassan, Rosli (2015)
The aim of this study is to identify the usage of digital reference service among students at an academic library in northern area . Libraries are the heart of the universities. Academic libraries are besieged to keep their place as the major source of inquiry in the face of emerging digital technology. Digital technology has revolutionized not only the information is packaged, processed , stored, and disseminated, but also how users seek and access information throu gh virtual environment. The revolution of technology also brought impact to the reference service in the library . The digital reference service in this study focused on chat reference and electronic mail service . Quantitative method was used to carry out this study. The purpose of this study is to identify awareness and usag e of digital reference service, users ' satisfaction on digital reference service, and factors which influenced users to use the collections . Descriptive statistical analysis was used to analyze data. Result of this study would indicate that undergraduate students were aware of digital reference service offered an academic library. Several characteristics of digital reference service were identified in order to identify users ' need. The finding also revealed that the level of usage and satisfaction regarding digital reference service. The result of this study will enable the management of the library to recognize the usage of digital reference service among students . The findings will be useful to address libraries in taking actions to encourage students to use digital reference service in order for them to seek information effectively and efficiently .